Analyses on the Changes of Grazing Capacity in the Three-River Headwaters Region of China under Various Climate Change Scenarios. (5th September 2013) - Zhang, Rongrong; Li, Zhaohua; Yuan, Yongwei; Li, Zhihui; Yin, Fang
Abstract : On the livestock production in the Three-River Headwaters region (TRHR) in the macrocontext of climatic change, this study analyzed the possible changing trends of the net primary productivity (NPP) of local grasslands under four RCPs scenarios (i.e., RCP2.6, RCP4.5, RCP6.0, and RCP8.5) during 2010–2030 with the model estimation, and the grass yield and theoretical grazing capacity under each scenario were further qualitatively and quantitatively analyzed. The results indicate that the grassland productivity in the TRHR will be unstable under all the four scenarios. The grassland productivity will be greatly influenced by the fluctuations of precipitation and the temperature fluctuations will also play an important role during some periods. The local grassland productivity will decrease to some degree during 2010–2020 and then will fluctuate and increase slowly during 2020–2030.The theoretical grazing capacity was analyzed in this study and calculated on the basis of the grass yield. The result indicates that the theoretical grazing capacity ranges from 4 million sheep to 5 million sheep under the four scenarios and it can provide quantitative information reference for decision making on how to determine the reasonable grazing capacity, promote the sustainable development of grasslands, and so forth.